Innovation Promotion Fund supports the best researchers - Poletaev, G. M.; Kabanov, D. D. (Perm Federal Research Centre Journal, 2019)
The article observes the historical background of the “UMNIK” Contest in the Perm region. For the period of the Contest holding the Innovation Promotion Fund has supported a lot of young researchers who later became successful businessmen and now are famous not only in the Perm region but all over the world.